Avaliação crítica do processo de implementação e amadurecimento de um sistema de gestão da qualidade integrado BPL (Boas Práticas de Laboratório) e ISO/IEC 17025 - Prada, Patrícia Regina (2013)
The tests and/or study laboratories have sought the implementation of Quality Management Systems (QMS) in order to obtain a differential, which is the greater reliability and acceptance of their results. The two main systems adopted in laboratories are the Good Laboratory Practices (GLP), which guidelines are defined in NIT-DICLA-035, and ISO/IEC 17025, according to NBR ISO/IEC 17025. Comparatively, the guidelines of both standards, in respect to the experimental stage of laboratory, have the same goal, to guarantee the quality of the results. The systems differ in that the ISO/IEC 17025 operates in the laboratory routine activities as a whole, in contrast GLP focus is to serve as a base to a study that is accomplished. An analysis of the elements of the standards shows that there is substantial overlap in both of the requirements, which makes it possible to maintain a single and integrated system. Thus, this paper aims to analyze critically the implementation and maturation process of an integrated QMS according to GLP and ISO/IEC 17025 implemented in a Laboratory that performs tests of pesticides and veterinary products residues using chromatography. The system implementation was done in stages, and the activities performed in each one were evaluated. The first step consisted in defining the quality assurance team. Next it was defined the work scope, followed by the steps: analysis of the similarities between the standards and structuring of a system; adaptation and elaboration of documentation to comply with the integrated system, with emphasis on the methods validation and uncertainty estimation procedures; training; audits; critical analysis meeting by management and finally organize the documentation for submission to INMETRO. During the implementation process it was conducted a survey among collaborators about the difficulties and benefits of the process. In addition, it was evaluated the time required to implement the system, the period to get the formal recognition and audit data, such as noncompliance highlighted and corrective actions taken. These data were compared with those obtained in Brazil and the USA laboratories.